(untitled) (Theatrum historiae, 2013)
The article that is based on travel diaries, personal calendars and correspondence deals with count Franz of Thun-Hohenstein (1809–1870) and his journey to Western Europe (1833–1835). Its main purpose was to visit England, Scotland and Ireland. The journey of Franz and his two brothers was organized by their father Franz Anton of Thun-Hohenstein who followed the example of his own journey from 1806. The author does not want to describe minutely the journey, she rather desires to analyse the reflection of the phenomenon of family journey by young count Franz. He could not travel on his own because he was supervised by his father and had to conform family demands (they travelled also together with his mother and sisters). The author focuses mainly on relationship between Franz and his father and interprets it in the context of their later conflict.